Determinants of E-Commerce Adoption in Ethiopia: The Case of Tele-birr Transaction in Addis Ababa - Biruk Tessema, Swati Prasad (Journal of Informatics Education and Research, 2024)
Issue: This research aims to examine the major determinant factors influencing e-commerce adoption in Telebirr, Addis Ababa. Method: An explanatory and descriptive research approach was employed to analyze the data collected using a 5-point Likert scale questionnaire. The data was collected from consumers, sellers, service providers, and Telebirr agents in Addis Ababa. Finding: The results from the descriptive statistics analysis showed that user-friendliness-related factors, functionality-related factors, and consumers’ persona-related factors play a crucial role in the adoption of e-commerce in Telebirr. On the other hand, perceived risk-related factors do not seem to be a significant concern for consumers in the context of e-commerce. Furthermore, the correlation analysis results suggest that user-friendliness related, functionality-related, and consumers' persona-related factors have a significant positive correlation with e-commerce adoption. Multiple regression analysis results showed that all four factors (user friendliness-related, functionality related, perceived risk-related, and consumers’ persona-related factors) significantly contribute to the adoption of e-commerce by customers. Thus, the findings highlight the significance of user friendliness, functionality, personalized and customized services, and personal characteristics of users to enhance e-commerce adoption. Though the perceived risk-related factor was not found to be significantly correlated, e-commerce businesses should not overlook the importance of their customers' sense of security when using their e-commerce platforms. The results provide valuable insights for e-commerce businesses to design and implement more effective strategies to increase customers' adoption of their platforms.